Differential diagnosis of a large size tumor in the retroperitoneum: A case report of retroperitoneal lipoblastoma - Hisayuki Miyagi; Shohei Honda; Masashi Minato; Akihiro Iguchi; Emi Takakuwa; Akinobu Taketomi (Wolters Kluwer Medknow Publications, 2018)
Lipoblastoma can arise almost anywhere within the soft tissues, especially in the extremities. It is rarely seen retroperitoneally. A 3-year-old girl presented with a palpable abdominal mass underwent an exploratory laparotomy with resection of the retroperitoneal mass. Based on histopathologic and cytogenetic features, a final diagnosis of lipoblastoma was rendered. At 18-month follow-up, she had no evidence of recurrence.